2003
DOI: 10.1046/j.1365-2249.2003.02284.x
|View full text |Cite
|
Sign up to set email alerts
|

No strong relationship between mannan binding lectin or plasma ficolins and chemotherapy-related infections

Abstract: SUMMARYChemotherapy causes neutropenia and an increased susceptibility to infection. Recent reports indicate that mannan-binding lectin (MBL) insufficiency is associated with an increased duration of febrile neutropenia and incidence of serious infections following chemotherapy for haematological malignancies. We aimed to confirm or refute this finding and to extend the investigation to the plasma ficolins, P35 (Lficolin) and the Hakata antigen (H-ficolin). MBL, L-ficolin and H-ficolin were measured in 128 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 15 publications
6
62
1
3
Order By: Relevance
“…The condition with more reduced dose of chemotherapy, conventional-dose chemotherapy without stem cell support, has been demonstrated to be at an increased risk of infection or prolonged fever in several reports, 13,14 but not by others. 17,27 Considering the strong association of MBL polymorphism and major bacterial infection in our patients, it is suggested that the protective role of MBL for infection might be more pronounced in the patients receiving HDT than those with conventional chemotherapy. However, it should be taken into consideration that the controversy about the relationship of MBL deficiency and infection after chemotherapy might be caused, at least in part, by the difference in the patients' profiles, such as underlying diseases, age, ethnicity, and other unknown genetic factors, between these several studies including ours.…”
Section: Increased Risk Of Infection In Mbl Polymorphismmentioning
confidence: 83%
See 1 more Smart Citation
“…The condition with more reduced dose of chemotherapy, conventional-dose chemotherapy without stem cell support, has been demonstrated to be at an increased risk of infection or prolonged fever in several reports, 13,14 but not by others. 17,27 Considering the strong association of MBL polymorphism and major bacterial infection in our patients, it is suggested that the protective role of MBL for infection might be more pronounced in the patients receiving HDT than those with conventional chemotherapy. However, it should be taken into consideration that the controversy about the relationship of MBL deficiency and infection after chemotherapy might be caused, at least in part, by the difference in the patients' profiles, such as underlying diseases, age, ethnicity, and other unknown genetic factors, between these several studies including ours.…”
Section: Increased Risk Of Infection In Mbl Polymorphismmentioning
confidence: 83%
“…11,12 An association of MBL deficiency and infection is also reported in patients treated with conventional chemotherapy 13,14 or high-dose myeloablative chemotherapy followed by allogeneic stem cell transplantation, 15 which is not confirmed by others. 16,17 In the present study, we report an increased risk of major bacterial infection in patients carrying the MBL polymorphism when treated with high-dose chemotherapy (HDT) followed by autologous peripheral blood stem cell transplantation (auto-PBSCT). In addition, the allele frequencies of the MBL polymorphism in a total of 2623 healthy individuals were determined in seven different areas in Japan, which is, to our knowledge, the largest scale of study for MBL polymorphism in a single ethnic group.…”
mentioning
confidence: 74%
“…9 From the small subset (21/128) of those patients who were treated with allogeneic haemopoietic stem cell transplantation, six had MBL concentrations p100 ng/ml around the time of neutropenia. One of the patients had since died and another died while ethical permission was being requested to approach the donors.…”
Section: Methodsmentioning
confidence: 99%
“…9 From that previous study, six patients with barely detectable serum MBL who received an allogeneic stem cell transplant were identified. Therefore, by taking blood samples from the donors, it would be possible to establish if any of them had MBL concentrations significantly higher than the corresponding patients and, if so, by taking a further blood sample from the patients (recipients), it should be possible to establish if any patient seroconverted to a higher MBL concentration as a result of the transplant.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] However, these observations are not consistent in all studied cohorts. [9][10][11] Few studies have included hematopoietic SCT (HSCT) recipients 7,8,10 or have focused on children. 4,6,9 MBL deficiency can be corrected by liver transplantation, whereas MBL deficiency can be induced by transplantation of MBL-sufficient recipients with an MBL-deficient donor liver.…”
Section: Introductionmentioning
confidence: 99%